Evaluation of the effects of venlafaxine and pregabalin on the carbon dioxide inhalation models of Generalised Anxiety Disorder and panic. (February 2013) - Diaper, Alison; Osman-Hicks, Victoria; Rich, Ann S; Craig, Kevin; Dourish, Colin T; Dawson, Gerard R; Nutt, David J; Bailey, Jayne E
Previous studies have shown that subjective and objective symptoms of anxiety induced by 7.5% CO2 inhalation can be attenuated by anxiolytics such as lorazepam and, to a lesser extent, paroxetine. Venlafaxine and pregabalin, two other licensed treatments for Generalised Anxiety Disorder, were used to further investigate the 7.5% and 35% CO2 models of anxiety in healthy volunteers. Fifty-four participants were randomised to receive either placebo, venlafaxine or pregabalin. Study treatments were dosed incrementally over a three week period, to reach daily doses of 150mg venlafaxine and 200mg pregabalin by the CO2 challenge test day. Participants inhaled air 7.5% CO2 for 20 minutes (single-blind presentation), and a non-blinded single vital capacity of 35% CO2 . Subjective ratings were recorded before and after each inhalation. Both 7.5% and 35% CO2 inhalations produced the expected effects of increased ratings of symptoms of panic and anxiety, with increased blood pressure and heart rate. No significant treatment effects were found, although there were trends towards a reduction in feeling tense and nervous by both drugs compared with placebo during the 7.5% CO2 challenge, and a reduction in alertness generally in the venlafaxine group compared with the pregabalin group. In contrast with the clear anxiolytic effects of benzodiazepines reported in several previous CO2 studies, these findings suggest that the anxiogenic effects of CO2 challenges are not significantly influenced by these serotonergic and GABAergic anxiolytics. This may be due to a lack of sensitivity of the CO2 challenges in healthy volunteers to these drug types.